Evaluation of Current Music Synthesis Software for Rendering of Various Synthesis Algorithms - Tan, Julie Lee Mei (2000)
The ability to distinguish the usefulness of currently available music synthesis software for the application of various synthesis algorithms is the main focus of the research. The amplitude modulation (AM), ring modulation (RM), frequency modulation (PM), additive synthesis and granular synthesis algorithms were used and applied into the Wave Craft [specialised graphical user interface software], Cool Edit Pro [digital audio editor software] and Csound [command prompt type software] synthesis software. These softwares were chosen and categorised according to the software interface. Cool Edit Pro, a commercial or digital audio editor and not specifically a synthesis software, can however be used for this purpose. Due to the accelerated development in music synthesis software, there is an increasing number of new software now with no precise definition of software characteristics to determine their usefulness has been described. Thus, in this project, a Music Software Evaluation (MSE) metrics table with exact definition and criteria in determining the usefulness of music synthesis software was designed and used to evaluate the usefulness of these softwares. Questionnaires were designed based on the MSE metrics table to gauge information on the different features available in the three music synthesis software and also from individuals about their expectations and experience with regards to the softwares. Results from these research findings indicate that different music synthesis software provides users with different features. The results also showed that, from user expectations point of view, Cool Edit Pro is the most preferred software. For experienced users, Csound is preferred over Cool Edit Pro. Conclusions drawn from this research finding is that different software approaches fulfill different kinds of user expectations depending on user experience.